ON IMPROVING THE ENERGY SUPPLY OF BATCH DYEING APPARATUSES IN THE LIGHT INDUSTRY ENTERPRISES - V. N. Romaniuk; D. B. Muslina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper offers the results of pinch analysis, thermodynamic analysis based on exergy method that determine the energy-supply efficacy enhancement variants for the processing equipment in the light industry finishing production as exemplified by the apparatuses of batch operation for textile dyeing. Scientifically substantiated improvement feasibility estimation for the Belarusian light industry enterprises thermo-technological production energy supply is of current concern and in demand in the existing economic situation. Exergy method allows obtaining the indicated estimation by the simplest and most logical way as against the other methods of thermodynamic analysis e.g. entropy method or employing the cycle theory. Pinch analysis employment not only allows verifying the estimation results but also points out the problem spots demanding cardinal changes and modernization. This complex approach renders possible outlining simple ways of energy saving in the existing technical systems of substance transformation, which is important under the conditions of operating production for successful handling the problem of lowering production costs. The example of the most widespread thermo-technological production of the light industry illustrates the above stated. For most enterprises of the republic, it remains problematic in many ways. The suggested ways of solving the problem are not exhaustive and offer evolutionary changes that secure economic indicators fitting the dictates of time and the enterprises capabilities. Another critical factor of the presented analysis and ways for thermo-technological energy supply improvement is that the proposed changes can realize on basis of the equipment that established a good reputation during continuous service in different productions and manufactured in the republic in working partnership with foreign design engineers.